Metodologias ativas em espaços educativos: processos de alfabetização científica em laboratórios móveis do projeto academia stem - Silva, Andreza Carvalho da (2022)
This study addresses issues related to Active Methodologies in Non-Formal Spaces as a progression process of Scientific Literacy of engineering students. Bearing in mind that the world is in a moment of frequent transmutations with fleeting scientific and technological progress, it is essential to promote teaching methodologies that provide the development of skills and competences that make them manage this avalanche that emerges in the professional and social field. , since only specific technical knowledge does not constitute a pleasant engineer for the 21st century, who can visualize global demands. Given the theme, the general objective of the research is to investigate how the development of Active Methodologies in Non-Formal Spaces can contribute to the process of Scientific Literacy of students of the engineering course, scholarship holders in the Academia STEM Project of the State University of Amazonas. The research methodology is based on a qualitative approach, following participant observation techniques, a questionnaire with open questions and dialogue groups. The results allowed us to point out that the active methodology used in the Mobile Laboratories of the Academia STEM Project is Jigsaw, which obtain reading, writing, research, experience, teaching, dialogue, doubt, reflection, problem solving and planning activities that culminate in the development of skills and skills that make up an engineer able to deal with the social and professional field of the 21st century, such as: creativity, proactivity, autonomy, responsibility, cooperation, interaction and versatility. With this, the academics participating in the current study, in the Itinerant Mobile Laboratories of the STEM Academy Project, build their own knowledge, resulting in autonomy and Scientific Literacy, since the students, in addition to using the scientific vocabulary, are able to mobilize the specific technical concepts they have learned to their reality, giving applicability to everyday problems. In this way, we found that the active methodologies developed in the Mobile Laboratories of the Academia STEM Project provide the training of engineers who are more than technical specialists in certain themes, but emancipated citizens who are able to carry out a proper reading of the natural world, based on scientific knowledge in social and professional practices. Keywords: Active Methodology. Non-Formal Space. Scientific Literacy. Projeto Academia STEM.